The wall behind China's open door : sustainable management and long term strategies in China - Boden, Jeanne, 1957- (Brussels : ASP nv (Academic & Scientific Publishers), 2015)
An excellent guide for anyone working with China, highlighting China's economic, legal, political, social and cultural contexts. This second, improved and updated edition, provides in-depth insight in how to successfully do business with China. The book has become a benchmark for business people dealing with China.
Includes bibliographical references (pages 230-233) and index.
Keywords: China ; management